Enkens søn fra Nain - Thaning, Kaj (Grundtvig-Studier, 1989)
The Son of the Widow from Nain. By Kaj Thaning This article intends to elucidate the distinctions that Grundtvig made in his world of ideas in the course of the years from 1824 to 1834, first between spirit and letter, church and church-school (1826-1830), and then between natural life and Christian life (in 1832). In His "Literary Testament" (1827), Grundtvig himself admits that there was a "Chaos" in his writings, due to the youthful fervour that pervaded his literary works and his sermons in the years 1822-1824. But not until 1832 does he acknowledge that "when I speak or write as a citizen, or a bard, or a scholar, it is not the time nor the place to either preach or confess, so when I have done so, it was a mistake which can only be excused with the all too familiar disorder pertaining to our church, our civic life, and our scholarship...", as it says in a passage omitted from the manuscript for "Norse Mythology”, 1832. (The passage is printed in its entirety in ”A Human first...”, p. 259f.) The point of departure for Thaning’s article is a sermon on the Son of the Widow from Nain, delivered in 1834, which the editor, Christian Thodberg also found "singularly personal”, since Grundtvig keeps using the pronoun ”1”. In this sermon Grundtvig says that those who have heard him preaching on this text before, would remember that he regarded the mourning widow as ”an image of the same broken heart at all times”, and her comforter, Jesus, not only as a great prophet in Israel, but ”as the living Being who sees us and is with us always until the end of the world”. Thodberg is of the opinion that Grundtvig refers to his sermon from 1823. Thaning, however, thinks that the reference is to the sermon from 1824. But Grundtvig adds that one may now rightly ask him whether he ’’still regards the gospel for the day with the same eyes, the same hope and fear as before.” He wants to discuss this, among other things ’’because the best thing we can do when we grow old is ... to develop and explain what in the days of our youth .. sprang up before our eyes and echoes in our innermost mind.” In other words, he speaks as if he had grown old. So Thaning asks: "What happened on the way from Our Saviour’s Church to Frederick’s Church?" Thaning’s answer is that there was a change in Grundtvig’s view of life. Already in his first sermon in 1832, he says that his final and truly real hour as a pastor has now arrived. Thaning’s explanation is that Grundtvig has now passed from the time of strong emotions to that of calm reflections. Not until now does he realize "what is essential and what is not". And in 1834 he says that our Christian views, too, must go through a purgatorial fire when we grow older. This is not only true of the lofty views of human life which, naturally, go through this purgatory and most often lose themselves in it. Here Grundtvig distinguishes between natural and Christian life which is something new in a sermon. Thaning adds that this purgatorial fire pervades Grundtvig’s drafts for the Introduction to "Norse Mythology" in 1832. But then, Grundtvig’s lofty views did not lose themselves in purgatory. He got through it. His view of life changed. (Here Thaning refers to his dissertation, "A Human First...", p. 306ff). This is vaguely perceptible throughout the sermon in question. But according to Thaning Grundtvig slightly distorts the picture of his old sermon. In the latter he did not mix up natural and Christian life. It is Thaning’s view that Grundtvig is thinking of the distinct mixture of Christianity and Danish national feeling in the poem "New Year’s Morning" (1824). But he also refers to Grundtvig’s sermon on Easter Monday, 1824, printed in Helge Toldberg’s dissertation, "Grundtvig’s World of Symbols" (1950), p. 233ff, showing that he has been captured by imagery in a novel manner. He seems to want to impose himself upon his audience. In 1834 he knows he has changed. But 1832 is the dividing year. In the passage omitted from the manuscript for "Norse Mythology", Grundtvig states explicitly that faith is "a free matter": "Faith is a matter of its own, and truly each man’s own matter". Grundtvig could not say this before 1832. Thaning is of the opinion that this new insight lies behind the distinction that he makes in the sermon in 1834, where he says that he used to mix up Christian life with "the natural life of our people", which involved the risk that his Christian view might be misinterpreted and doubted. Now it has been through purgatory. And in the process it has only lost its "absurdity and obscurity, which did not come from the Lord, but from myself”. Later in the sermon he says: "The view is no more obscured by my Danish national feeling; I certainly do not by any means fail to appreciate the particularly friendly relationship that has prevailed through centuries between the Christian faith and the life of this people, and nor do I by any means renounce my hope that the rebirth of Christianity here will become apparent to the world, too, as a good deed, but yet this is only a dream, and the prophet will by no means tell us such dreams, but he bids us separate them sharply from the word of God, like the straw from the grain...". This cannot be polemically directed against his own sermons from 1824. It must necessarily reflect a reaction against the fundamental view expressed in "New Year’s Morning" and its vision of Christianity and Danishness in one. (Note that in his dissertation for the Degree of Divinity, Bent Christensen calls the poem "a dream", as Thaning adds). In his "Literary Testament" (1827) Grundtvig speaks about the "Chaos" caused by "the spirits of the Bible, of history, and of the Nordic countries, whom I serve and confuse in turn." But there is not yet any recognition of the same need for a distinction between Danishness and Christianity, which in the sermon he calls "the straw and the grain". Here he speaks of the distinction between "church and church-school, Christianity and theology, the spirit of the Bible and the letter of the Bible", as a consequence of his discovery in 1825. He still identifies the spirit of human history with the spirit of the Bible: "Here is the explanation over my chaos", Grundtvig says. But it is this chaos that resolves itself, leading to the insight and understanding in the sermon from 1834. In the year after "The Literary Testament", 1828, Grundtvig publishes the second part of his "Sunday Book", in which the only sermon on the Son of the Widow in this work appears. It is the last sermon in this volume, and it is an elaboration of the sermon from 1824. What is particularly characteristic of it is its talk about hope. "When the heart sees its hope at death’s door, where is comfort to be found for it, save in a divine voice, intoning Weep not!" Here Grundtvig quotes St. John 3:16 and says that when this "word of Life" is heard, when hope revives and rises from its bier, is it not then, and not until then, that we feel that God has visited his people...?" In the edition of this sermon in the "Sunday Book" a note of doubt has slipped in which did not occur in the original sermon from 1824. The conclusion of the sermon bears evidence that penitential Christianity has not yet been overcome: "What death would be too hard a transition to eternal life?" - "Then, in the march of time, let it stand, that great hope which is created by the Word ... like the son of the great woman from Nain." It is a strange transition to go from this sermon to the next one about the son of the widow, the sermon from 1832, where Christ is no longer called "hope". The faith has been moved to the present: "... only in the Word do we find him, the Word was the sign of life when we rose from the dead, and if we fell silent, it was the sign of death." - "Therefore, as the Lord has visited us and has opened our mouths, we shall speak about him always, in the certain knowledge that it is as necessary and as pleasurable as to breathe..." The emphasis of faith is no longer in words like longing and hope. In a sense this and other sermons in the 1830s anticipate the hymn "The Lord has visited his people" ("Hymn Book" (Sangv.rk) I, no. 23): the night has turned into morning, the sorrow has been removed. The gospel has become the present. As before the Church is compared with the widow who cried herself blind at the foot of the cross. Therefore the Saviour lay in the black earth, nights and days long. But now the Word of life has risen from the dead and shall no more taste death. The dismissal of the traditional Christianity, handed down from the past, is extended to include the destructive teaching in schools. The young man on the bier has been compared with the dead Christianity which Grundtvig now rejects. At an early stage Grundtvig was aware of its effects, such as in the Easter sermon in 1830 ("Sunday Book" III, p. 263) where Grundtvig speaks as if he had experienced a breakthrough to his new view. So, the discovery of the Apostles’ Creed in 1825 must have been an enormous feeling of liberation for him – from the worship of the letter that so pervaded his age. Grundtvig speaks about the "living, certain, oral, audible" word in contrast to the "dead, uncertain, written, mute" sign in the book. However, there is as yet no mention of the "Word from the Mouth of our Lord", which belongs to a much later time. Only then does he acquire the calm confidence that enables him to preach on the background of what has happened that the Word has risen from the dead. The question to ask then is what gave him this conviction. "Personally I think that it came to him at the same time as life became a present reality for him through the journeys to England," Thaning says. By the same token, Christianity also became a present reality. The discovery of 1825 was readily at hand to grant him a means of expression to convey this present reality and the address to him "from the Lord’s own mouth", on which he was to live. It is no longer enough for him to speak about "the living, solemn evidence at baptism of the whole congregation, the faith we are all to share and confess" as much more certain than everything that is written in all the books of the world. The "Sunday Book" is far from containing the serene insight which, in spite of everything, the Easter sermon, written incidentally on Easter Day, bears witness to. But in 1830 he was not yet ready to sing "The Lord has visited his people", says Thaning. In the sermon from 1834 one meets, as so often in Grundtvig, his emphasis on the continuity in his preaching. In the mourning widow he has always seen an image of the Church, as it appears for the first time in an addition to the sermon on the text in the year 1821 ("Pr.st. Sermons", vol I, p. 296). It ends with a clue: "The Church of Christ now is the Widow of Nain". He will probably have elaborated that idea and concluded his sermon with it. Nevertheless, as it has appeared, the sermon in 1834 is polemically directed against his former view, the mixture of Christian and natural life. He recognizes that there is an element of "something fantastic" sticking to the "view of our youth". Already in a draft for a sermon from March 4,1832, Grundtvig says:"... this was truly a great error among us that we contented ourselves with an obscure and indefinite idea of the Spirit as well as the Truth, for as a consequence of that we were so doubtful and despondent, and we so often mistook the letter for the spirit, or the spirit of phantasy and delusion for that of God..." (vol. V, p. 79f). The heart-searchings which this sermon draft and the sermon on the 16th Sunday after Trinity are evidence of, provide enough argument to point to 1832 as a year of breakthrough. We, his readers, would not have been able to indicate the difference between before and now with stronger expressions than Grundtvig’s own. "He must really have turned into a different kind of person", Thaning says. At the conclusion of the article attention is drawn to the fact that the image of the Son of the Widow also appears in an entirely different context than that of the sermon, viz. in the article about Popular Life and Christianity that Grundtvig wrote in 1847. "What still remains alive of Danish national feeling is exactly like the disconsolate widow at the gate of Nain who follows her only begotten son to the grave" (US DC, p. 86f). The dead youth should not be spoken to about the way to eternal life, but a "Rise!" should be pronounced, and that apparently means: become a living person! On this occasion Grundtvig found an opportunity to clarify his ideas. His "popular life first" is an extension of his "a human being first" from 1837. He had progressed over the last ten years. But the foundation was laid with the distinction between Christian and natural life at the beginning of the 1830s.